UPAYA DOSEN PENDIDIKAN AGAMA ISLAM DALAM MENYIAPKAN MAHASISWA MENGAHADAPI TANTANGAN DIGITAL - Prima aode putra; Fakhruddin; Karliana indrawari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of information technology has transformed the educational paradigm, influencing the way students learn and demanding adjustments from educators, especially in Islamic Religious Education (PAI) courses. This research aims to uncover the digital challenges faced by students and the teaching methods applied by PAI educators in preparing students for the digital era. The study seeks to discover solutions and recommend teaching methods that can integrate religious values with technological challenges, enabling students to understand and navigate the digital era wisely. The implications of this research are expected to contribute to the development of relevant teaching methods in PAI courses amidst the current digital era. This qualitative descriptive research involves PAI lecturers at IAIN Curup, selected through purposive sampling. Data collection methods include observation, interviews, and documentation, aiming to reveal the challenges, obstacles, and efforts made by educators in adapting to technological changes in the learning process. Triangulation of sources is used to ensure the credibility of the obtained data. Islamic Education Students at IAIN Curup face digital challenges in the learning process. Issues of technological awareness, optimal use of technology, and 'copypaste' tendencies are in focus. The integration of technology in the curriculum, limited access, and the negative impact of digital advances are obstacles. Understanding ethics and morals, as well as policies for choosing digital media, are the keys to improving learning. Traditional learning methods remain relevant, and other learning methods can also be combined with technology. Access to devices such as smartphones and AI (Artificial Intelligence) is supportive, but infrastructure constraints and lack of awareness of digital trends are obstacles. Students must overcome a lack of technology skills. Challenges involve human resources, technology, and internet access.